2021
DOI: 10.21203/rs.3.rs-269828/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementing supportive exercise interventions in the colorectal cancer care pathway: a process evaluation of the PREPARE-ABC randomised controlled trial.

Abstract: Background: A colorectal resection is standard treatment for patients with colorectal cancer (CRC). However, the procedure results in significant post-operative mortality and reduced quality of life. Maximising pre-operative cardiopulmonary fitness could improve post-surgical outcomes. PREPARE-ABC is a multi-centre, three-armed, randomised controlled trial investigating the effects of exercise interventions, with motivational support on short and longer-term recovery outcomes in CRC patients undergoing major l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Success was mainly due to the visionary leadership and diverse and committed group of interdisciplinary professionals working together to adapt and refine a tailored stepped-care MCPP for local implementation at a Cancer Unit in Northern Ireland [14]. Current research investigating the feasibility and acceptability of MCPPs from the perspectives of professionals and patients is exceptionally limited [17] with studies often referring to patient recruitment and participation as indicators of success [23-24]. The findings from this study extend current evidence by illustrating the mechanisms of success and challenges experienced by those at SET and will be discussed through the lens of NPT components [20], coherence, cognitive participation, collective action and reflexive monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Success was mainly due to the visionary leadership and diverse and committed group of interdisciplinary professionals working together to adapt and refine a tailored stepped-care MCPP for local implementation at a Cancer Unit in Northern Ireland [14]. Current research investigating the feasibility and acceptability of MCPPs from the perspectives of professionals and patients is exceptionally limited [17] with studies often referring to patient recruitment and participation as indicators of success [23-24]. The findings from this study extend current evidence by illustrating the mechanisms of success and challenges experienced by those at SET and will be discussed through the lens of NPT components [20], coherence, cognitive participation, collective action and reflexive monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Murdoch et al . [17] study of their MCPP with a CRC patient group suggested that while professionals emphasised that fitness was important for surgery outcomes, patients were not encouraged to increase activity levels. Herein, they noted that the lack of exercise prescription was attributed to a short timeframe between diagnosis and treatment, plus constrained resources with clinicians being too busy [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations